PSI-10 Genetic parameters for soybean allergy response in divergently-selected pigs - Chen, Yuwen (J Anim Sci, 2020)
Genetically selecting for improved animal resilience has become of great interest in modern livestock breeding. In this context, piglets experience a transitory allergic response to soybean proteins that has a negative impact on their growth and welfare. The main objective of this study was to determine whether soybean allergy response is a heritable trait, using divergently selected pig lines. The base generation pigs were generated from nine sire lines (primarily Yorkshire and Landrace) and two dam sources (Yorkshire × Chester White F1 and Landrace × Yorkshire F1). Soybean allergic response was measured, following a skin test protocol, on pigs that received a diet containing 28% soybean meal for 21 consecutive days post-weaning. The skin test was performed with an intradermal injection of soybean protein. Wheel and flare scores (ranging from 0 to 3) were assigned approximately 60 minutes post-injection. Based on the skin test total scores (i.e., the sum of the wheal and flair scores, ranging from 0 to 6), animals were selected to create two (a high and a low) soybean protein reacting lines, and bred within lines for nine generations. Phenotypes used in this study were measured on a total of 5,505 animals born from generations one to nine, in both high and low reacting lines. Significant systematic effects (P < 0.05) included in the statistical model were birth year, birth season, sex, and weaning weight (as a covariate). Genetic parameters for the skin test were estimated using a pedigree-based relationship matrix containing 9,201 animals, and a threshold animal mixed model. The genetic variance estimated for soybean allergy was 0.091, indicating that there is genetic variability in this trait. The heritability estimated for soybean allergy response was 0.139, which indicates that food allergy response is a heritable trait and can be improved through selective breeding.